Correlation of Self Efficacy with Entrepreneurial Attitudes of Science Teacher Candidates - M. Khairul Wazni; Agus Muliadi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to determine the correlation of self-efficacy with student attitudes in the field of entrepreneurship. This study is a descriptive exploratory study with 35 biology education students as subjects. The research instrument used was a closed questionnaire with degraded answers according to a Likert scale that had been validated by experts and declared valid. Analysis of the research data used is descriptive statistics and inferential statistics with a product moment (rxy) correlation test at a significance level of 5%. The study results show that (1) students' perceptions about self-efficacy has an average score of 3.12 in the Good category and an entrepreneurial attitude of 3.06 in the Good category; (2) there is a significant relationship between self-efficacy and student attitudes in the field of entrepreneurship with a significance value of 0.000 which is smaller than the alpha testing value of 0.05 (<0.05); (3) the value of the correlation coefficient is 0.803, which means that the relationship is very strong between self-efficacy and student attitudes in the field of entrepreneurship.